Hijrah and the articulation of Islamic identity of Indonesian millenials on Instagram - Rahman, Taufiqur; Frizki Yulianti Nurnisya,; Adhianty Nurjanah,; Lailia Hifziati, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper focuses on Indonesian millennial Muslims’ experience in using Instagram and how this influenced their hijrah and the articulation of Islamic identity as millennial Muslims. Historically, the term hijrah is traced to the commemoration of the day when the Prophet Muhammad (PBUH) emigrated from Makkah to Madinah. The term is translated as emigration, but then interpreted differently by Muslims in many parts of the world. On the one hand, the term has been used by violent Muslim groups such as ISIS to persuade Muslims to emigrate to the so-called Islamic State. On the other hand, the young generation of Muslims use it to declare a spiritual emigration and pursue a better life. This paper asks how millennial Muslims in Indonesia interpret the term hijrah and how they articulate the idea of hijrah and their Islamic identity into their activities on Instagram. The study employs critical discourse analysis as its primary and virtual ethnography as a secondary research method to reveal the articulation of the term hijrah in social media by millennial Muslims in Indonesia. This study indicates that the spirit of hijrah in Instagram by millennial Muslims is more about a spiritual journey rather than a political movement. The hijrah phenomenon on Instagram was also celebrated differently by informants, considering the cultural background, gender, parental education, living environment, and education, which affected the migration process differently.